Can caffeine supplementation reverse the impact of time of day on cognitive and short-term high intensity performances in young female handball players? - Bougrine, H.; Cherif, M.; Chtourou, H.; Souissi, N. (Chronobiology International, 2022)
The aim of the present study was to explore whether caffeine (CAF) intake counteracts the morning reduction in cognitive and short-term maximal physical performances related to the daily variation pattern in young female handball players. In a randomized order, 15 active young female handball players [mean (SD) age:16.3 ± 0.8 y, height: 166.1 ± 5.3 cm; body mass: 58.7 ± 9.1 kg; BMI: 21.3 ± 3.1 kg/m2] performed the simple reaction time (SRT), the attention (AT), the squat jump (SJ), the Illinois agility (IAT) and the 5 m run shuttles (to determine total (TD) and peak (PD) distances) tests at 08:00 h and 18:00 h, 60 min after a placebo (cellulose) or CAF (6 mg·kg-1) intake. The results revealed a significant diurnal variation during both the placebo and the CAF conditions, with improvement of cognitive and physical performances from 08:00 h to 18:00 h (P < .05). Moreover, the improvement of SRT and AT after CAF was better in the morning compared to the afternoon (e.g., 5.3% vs. 2.8% for SRT and 4.2% vs. 0.9% for AT). At 08:00 h and 18:00 h, SJ, IAT, TD, and PD were higher after CAF intake than Placebo (p < .05). This improvement was greater at 08:00 h than 18:00 h (e.g., 4.2% vs 1% for SJ, 1.6% vs 0.2% for IAT, 2.4% vs. 0.3% for TD, and 6% vs. 0.9% for PD). In conclusion, the dose of 6 mg·kg-1 CAF intake improves the cognitive and physical performances in young female handball players and reduces the intraday variation of these parameters.